Study and Communication Skills for College Freshmen : Worktext in English 1 - Ornos, Petra S.; Esgra, Cerila B.;Gomez, Nieva G.;Verde, Stanley P. (Makati City, Philippines : Grandwater Publication and Research Corporation, 2006)
This book is primarily designed for first year college students taking up English 1. This was written in accordance to the ultimate goal of language learning, and the ability to use the language in purposeful communication.
Unit I. Developing the study skills -- Unit II. Expanding basic skills in grammar for communicative skills -- Unit III. Phrases, clauses, paragraph D development.
Includes bibliographical references.
Keywords: ENGLISH LANGUAGE -- STUDY AND TEACHING